MEMBACA “TINUNG” DALAM FILM CA BAU KAN: ANALISIS WACANA KRITIS DALAM PERSPEKTIF GENDER - Fadhillah Sri Meutia (Fakultas Dakwah dan Komunikasi, 2017)
This paper attempted to describe the representation of women in Ca Bau Kan throughcritical discourse analysis coined by Sara Mills in analyzing films using genderperspective. Theory of construction of reality by Berger and Luckmann was used to viewhow women are depicted in the film. Through gender perspective in media, this articlereveals how film media constructs reality on women, who are associated with passiveness,obedience and dependence to men. It also discusses how the difference betweenmasculinity and femininity is preserved by media culture. Lastly, this paper ends with aconclusion on the importance of equality between men and women so that film industrycan represent women in the media better, provide gender perspective for the society,especially young Indonesian audience.